Holistic Islamic Early Childhood Education through the Integration of Islamic Values and Minangkabau Culture: A Content Analysis of Syekh Sulaiman Arrasuli’s Pedagogical Novel - Ramadhoni Aulia Gusli; Nunu Burhanuddin; Hayati; Soibatul Aslamiah Nasution; Muaddyl Akhyar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Early childhood education (ECE) in Islamic contexts increasingly faces the challenge of balancing religious value formation with contextually grounded pedagogical approaches, yet the educational thought of local Islamic scholars in Southeast Asia remains largely unexamined in the international literature. This study analyzed the values of early childhood Islamic education embedded in Syekh Sulaiman Arrasuli’s pedagogical novel Pedoman Hidup di Alam Minangkabau, specifically the section “Muhammad Arif Will Enter Religious School” (1938), using qualitative interpretive content analysis. The primary source was the Jawi-script Malay-Minangkabau text, accessed in a transliterated digital edition; secondary sources comprised Islamic education scholarship, ECE theory, and Minangkabau cultural studies. Data were analyzed through open coding, axial coding, and thematic synthesis; trustworthiness was established through repeated reading, theory triangulation, peer examination, and audit trail. Three interconnected themes were identified: (1) the urgency of knowledge-seeking from early age, conceptualized through a four-role social taxonomy (ʿalim, merchant, official, customary leader) that frames education as the foundation of responsible social participation; (2) a foundational ECE curriculum integrating aqidah (Islamic creed), fiqh literacy (halal/haram distinctions), akhlaq (moral character), and rational-critical reasoning; and (3) a contextual synthesis of Islamic values and Minangkabau adat (customary law) centered on adab (etiquette) toward teachers and parents, bounded by shariʿa compliance. The family, embodied by the single-mother figure Siti Budiman, is positioned as the indispensable first educational environment. The study demonstrates that Arrasuli’s pedagogical thought anticipates contemporary holistic Islamic ECE frameworks and offers a theoretically coherent, culturally grounded model for current Islamic early childhood curriculum development in Indonesia and comparable Muslim majority contexts.